SETS AS A VISION AND APPROACH TO LEARNING THROUGH FIELD STUDY AND SKYPE - Dian Nugraheni; Novida Pratiwi; Munzil Munzil; Muhardjito Muhardjito (Prodi Pendidikan IPA FMIPA Universitas Negeri Malang, 2023)
The goal of Learning Basic Chemistry 1 is to help students comprehend the notion of chemistry and how it relates to circumstances, daily life, and technology. It adopts the vision and methodology of SETS. With this effort, students gain literacy in science, environment, technology, and society needed in the present and the future. In blended learning, time and location restrictions during field lectures are removed for both students and lecturers by using Skype. The development research is produced in the form of YouTube channels and vlogs, which are the current features of digital learning. Increasing students' comprehension of chemistry in SETS by exposing them to it as a science and allowing them to engage with it directly is another significant benefit of SETS learning.